Analisa Penentuan Saham Terbaik Menggunakan Metode Analytic Hierarchy Process (AHP) - Romindo Romindo (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
The number of stock investors has increased from the past to the present. Likewise, the number of companies listed on the Indonesia Stock Exchange (IDX). What makes investors confused about choosing the best stock from the hundreds of stocks that are regulated on the IDX. The method used for the best stock is the Analytic Hierarchy Process (AHP) method. Investors will enter criteria that take into account the specified criteria and criteria. The criteria used to determine stocks are C1 = PER, C2 = PBV, C3 = DER, C4 = ROE and C5 = ROA. The results of research conducted in the second rank show that alternative A1 = CPIN is in the first rank with a Priority Vector of 0.6536, alternative A2 = JFPA is in the second rank with a Priority Vector of 0.2013 and alternative A3 = UTAMA is in the second rank. second rank. second rank. second rank. ranked third with a Priority Vector of 0.1452.